2022
DOI: 10.1038/s43018-022-00403-z
|View full text |Cite
|
Sign up to set email alerts
|

Structural variants shape driver combinations and outcomes in pediatric high-grade glioma

Abstract: Pediatric high-grade gliomas (pHGGs), encompassing hemispheric and diffuse midline gliomas (DMGs), remain a devastating disease. The last decade has revealed oncogenic drivers including single nucleotide variants (SNVs) in histones. However, the contribution of structural variants (SVs) to gliomagenesis has not been systematically explored due to limitations in early SV analysis approaches. Using SV algorithms, we recently created, we analyzed SVs in whole-genome sequences of 179 pHGGs including a novel cohort… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 117 publications
(227 reference statements)
5
29
0
Order By: Relevance
“…Previously published WGS data of tumors ICGC-GBM27, ICGC-GBM96 and ICGC-GBM60 are deposited at EGA00001001139, and WGS data for BT836 and BT869 have been published under dbGaP accession number phs002380.v1.p1 (ref. 84 ). H3-K27M DMG ChIP-seq data were utilized from GSE126319 (ref.…”
mentioning
confidence: 99%
“…Previously published WGS data of tumors ICGC-GBM27, ICGC-GBM96 and ICGC-GBM60 are deposited at EGA00001001139, and WGS data for BT836 and BT869 have been published under dbGaP accession number phs002380.v1.p1 (ref. 84 ). H3-K27M DMG ChIP-seq data were utilized from GSE126319 (ref.…”
mentioning
confidence: 99%
“…Collectively, we refer to these putative super enhancer regions as Rhabdoid Oncogenic MYC Enhancer (RhOME) and number them according to their position in the genome. Notably, in contrast to RhOME2, RhOME1 (PCAT1) and RhOME3 (CCDC26) were previously identified as MYC regulatory regions in other tumor entities [24][25][26] . Our Hi-C and 4C experiments thus revealed that in different MRT PDOs, distinct distal enhancers interacting with the MYC promoter are active (RhOME1-3).…”
Section: Patient Specific Super Enhancers Interact With Myc In Mrtmentioning
confidence: 87%
“…Raw mass-spectrometry data is available for download from https://massive.ucsd.edu/, accession numbers MSV000087736 (reviewer login: username, MSV000087736_reviewer; password, HISTH3_BioID) and MSV000089173 (reviewer login: username, MSV000089173_reviewer; password: H3_mutants). Whole genome sequencing data is available under EGAS00001000575, EGAS00001001139, EGAS00001000572, EGAS00001000192, and under dbGaP accession number phs002380.v1.p1 (Dubois et al, 2022). All other data are available in the main text or the supplemental information.…”
Section: Resource and Data Availabilitymentioning
confidence: 99%